Social-Emotional Learning: Modifications to a Social Skills Training Program for Adolescents with Moderate to Severe Communication Disorders (Global Journal of Human-Social Science, 2015)
Abstract not found
Keywords: social skills intervention; emotional intelligence; executive functioning